The receptor for advanced glycation end products (RAGE) affects T cell differentiation in OVA induced asthma. - Eitan M Akirav; Octavian Henegariu; Paula Preston-Hurlburt; Ann Marie Schmidt; Raphael Clynes; Kevan C Herold (PLoS ONE, 2014)
The receptor for glycation end products (RAGE) has been previously implicated in shaping the adaptive immune response. RAGE is expressed in T cells after activation and constitutively in T cells from patients with diabetes. The effects of RAGE on adaptive immune responses are not clear: Previous reports show that RAGE blockade affects Th1 responses. To clarify the role of RAGE in adaptive immune responses and the mechanisms of its effects, we examined whether RAGE plays a role in T cell activation in a Th2 response involving ovalbumin (OVA)-induced asthma in mice. WT and RAGE deficient wild-type and OT-II mice, expressing a T cell receptor specific for OVA, were immunized intranasally with OVA. Lung cellular infiltration and T cell responses were analyzed by immunostaining, FACS, and multiplex bead analyses for cytokines. RAGE deficient mice showed reduced cellular infiltration in the bronchial alveolar lavage fluid and impaired T cell activation in the mediastinal lymph nodes when compared with WT mice. In addition, RAGE deficiency resulted in reduced OT-II T cell infiltration of the lung and impaired IFNγ and IL-5 production when compared with WT mice and reduced infiltration when transferred into WT hosts. When cultured under conditions favoring the differentiation of T cells subsets, RAGE deficient T cells showed reduced production of IFNγ but increased production of IL-17. Our data show a stimulatory role for RAGE in T activation in OVA-induced asthma. This role is largely mediated by the effects of RAGE on T cell proliferation and differentiation. These findings suggest that RAGE may play a regulatory role in T cell responses following immune activation.